Telaah Terhadap Formulasi Perhitungan Awal Bulan dalam Kitab Klasik al-Mandzumah al-Daliyah Karya Muhammad Faqih Maskumambang - Rifki Muslim; Ahmad Izzuddin (Islamic Astronomy Department, Sharia and Law Faculty, 2023)
Determining the beginning of the month in Islam indeed occupies a very central position, because with this determination Muslims can carry out a ritual of worship in a certain month with reverence. The determination of the beginning of the month is inseparable from the role of the ulema who has expressed his thoughts in his work which specifically discusses the determination of the beginning of the month. Many methods have been adopted by the scholars in expressing their thoughts, ranging from simple methods that produce inaccurate calculations, to complex and detailed calculations that produce accurate calculations. Of course these scholars rely on clear sources with their scientific sanad. One of the scholars who expressed his thoughts on determining the beginning of the month was Kyai Faqih Maskumambang which he put in his book entitled al-Madzumah al-Daliyah fi Ma'rifati awail al-asyhuri al-Qamariyah. This study explores the calculations in the book, with the formulation of the problem: how are the calculations in the book al-Mandzumah? And examine what the advantages and disadvantages of the book. The results of this study found that the calculations are simple (urfi) while the advantages are easy to learn and understand. The drawback is that there is no detailed correction so that the calculation results are not very accurate